Energetics and phase diagrams of Fe-Cr and Co-Cr systems from first principles - Vreštzál J.; Houserová J.; Šob M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The first principles computations of the total energies of complex phases have been addressed recently. The structural energy differences, calculated by FLAPW (Full potential augmented plane wave) method, enable us to utilize a more complete physical information about total energy of intermetallic phases and to propose a new model for their thermodynamic description. Our approach is based on the two-sublattice model, similarly as for solid solution phases, but the structural energy differences for end-members in the metastable or unstable structures are obtained by means of first-principles electronic structure calculations. Phase diagrams of Fe-Cr and Co-Cr systems containing the intermetallic sigma-phase (5 inequivalent lattice sites, 30 atoms in repeat cell) are described here as an example of application of our new model.